Pengaruh Integritas Terhadap Kepuasan Kerja Aparatur Sipil Negara Pada Beberapa Instansi Pemerintahan di Kecamatan Matur Kabupaten Agam - Nadia Sri Wahyuni; Syamsir Syamsir (Jurnal Teori dan Riset Administrasi Publik, 2022)
This research was motivated by the low participation of the job satisfaction State Civil Apparatus in Matur Distric, Agam Regency. There are stiill many problems that occur to the state civil apparatus in Matur Distric due the large number of civil servants who fell dissatisfied with their work , and so that the work they do is not optimal anymore. Therefore, the goverment of the Matur District of Agam Regency is expected to pay more attention to the level of integrity of the state civil apparatus so that the existing agencies in the Matur Distric so that the job satisfaction of the state civil apparatus can be increased and maximized. This research was carried out in several institutions such as the sub-district office, the rekigious court office and the agricultural office in the Matur Distric, Agam Regency. The data collection techniques were carried out through interviews, observations and questionnaires. Based on the results of the research and discussion it was found that integrity has a significant influence on job satisfaction of state civil servants in Matur Distric, Agam Regency. Keywords: Integrity;Job Satisfaction